2018
DOI: 10.3390/app8020241
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Motion Learning Framework to Promote Social Engagement

Abstract: Featured Application: Robotic imitation during human-robot interaction can build interest, empathy, and trust in human participants, opening the door to a vast host of medical care applications. These include a safe and realistic platform for special needs children to practice social encounters, companionship for elderly or bedridden hospital patients, and reliable supervision of outpatients.Abstract: Imitation is a powerful component of communication between people, and it poses an important implication in im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Additionally, feminine robots are preferred by users. Another concern found in this study was to understand what the human is doing; however, the robot's appearance depends on its application, the user's age, and several other factors [33,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, feminine robots are preferred by users. Another concern found in this study was to understand what the human is doing; however, the robot's appearance depends on its application, the user's age, and several other factors [33,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial empathy is, therefore, a crucial topic in social robotics (Asada 2015 ). Our literature review shows that ServBots can identify customers' emotions (Pasternak et al 2021 ; Rincon et al 2019 ) and react emotionally to customers' actions (Kerruish 2021 ; Dumouchel 2017 ), facial expressions of emotions (Chumkamon et al 2016 ; Bagheri et al 2021 ; Burns et al 2018 ), vocabulary (Fung et al 2016 ), voice, and level of arousal (De Carolis et al 2017 ). In turn, ServBots can manifest empathy to customers through an interface display (Kerruish et al 2021 ), facial expressions of emotions (Konijn and Hoorn 2020 ; Menne and Schwab 2018 ; Pasternak et al 2021 ), speech, and voice (James et al 2020 ), small social movements like nodding (Sakurai et al 2020 ), supportive behaviors (Leite et al 2013a , b , 2014 ), cuteness (Dumouchel 2017 ), and friendliness (Niculescu et al 2013 ).…”
Section: Servbots' Capacity To Use Ij During Service Recovery: a Comp...mentioning
confidence: 97%
“…It was observed that human-human avoidance is quite similar to human-robot avoidance if robot follows the human interaction rules. On the same lines, Burns et al [21] proposed a framework to promote social engagement, where they conducted an experimental study. The participants in the study exhibited a higher level of engagement and the affirmative emotional state towards the robot which displayed imitation.…”
Section: Related Workmentioning
confidence: 99%